Zaniechanie ukarania z art. 16a i 16b k.k.s. — szczególne rodzaje czynnego żalu czy niepotrzebna kazuistyka? - Sawicki, Janusz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article is a theoretical study of waiving the penalty of a fiscal penal law violator or a fiscal offender. The issues addressed in the article present major problems that draw the attention of both theorists and practitioners in the field. The aim of the article is to evaluate the contemporary model of waiving the penalty that is formulated by the fiscal penal code within Articles 16, 16a and 16b. The author analyzes in detail the institutions described in the Fiscal Penal Code, Chapter 2: The basic type of active grief and its special types. The article ends with closing remarks, including general conclusions and assumptions that relate to the model of waiving the penalty of a fiscal penal law violator using the institution of active grief, which in turn can contribute to providing a proper solution to the issue.
Keywords: waiving penalty; fiscal penal law; active grief